Latvian verbs of speaking and their relations to evidentiality - Chojnicka, Joanna (Kalbotyra, 2017)
The paper offers a functional analysis of three Latvian verbs of speaking used in their indicative third person forms – saka, runā and stāsta ‘say(s), speak(s) and talk(s)’ – based on the Latvian language corpus online (www.korpuss.lv) and, additionally, on examples excerpted from Internet discourse. The article discusses semantic and syntactic similarities and differences between these words, the functions of particular constructions distinguished according to specific syntactic criteria (presence vs. absence of a subject), and the use of these verbs in combination with the Latvian verb form traditionally associated with (potential) evidential meanings, the oblique (atstāstījuma izteiksme). While the use of verbs of speaking for introducing reported speech is seen as unproblematic, the relationship between verba dicendi and evidentiality requires more attention and remains in focus throughout this study. In order to offer an in-depth overview of the nature of this relationship, the relations between reported speech and evidentiality, as well as the oblique and evidentiality, are also briefly considered. The paper concludes that the possibility of the three verbs functioning as evidential markers depends on considerations of theoretical/terminological nature (how to define evidentiality, should reported speech be considered part of it, etc.) and also, to some extent, on the way the subject is realized in verba dicendi constructions (specific human agent vs. non-specific empty subject and absent or zero subject).